DISTRIBUTION OF DERMATOPHYTE SPECIES CAUSING ONYCHOMYCOSIS IDENTIFIED BY MALDI-TOF MS AND SANGER SEQUENCING (Vietnam Journal of Community Medicine, 2026)
Background: Onychomycosis is a common infectious disease in the community, predominantly caused by dermatophyte fungi. Accurate identification of the causative dermatophyte species is essential for selecting appropriate antifungal therapy and shortening treatment duration. This study aimed to identify dermatophyte species causing onychomycosis in patients treated at the National Hospital of Dermatology and Venereology using conventional methods combined with MALDI-TOF MS and Sanger sequencing. Methods: A cross-sectional descriptive study was conducted on 149 patients diagnosed with onychomycosis at the National Hospital of Dermatology and Venereology from August 2022 to August 2023. Nail specimens were examined by direct microscopy, cultured, and identified using conventional morphology-based methods, combined with MALDI-TOF MS and Sanger sequencing. Results: The positive culture rate for dermatophytes was 26.2% (39/149 samples). Conventional methods identified 27/39 isolates to the species level, accounting for 69.2%, while the remaining 12 isolates were identified only to the genus level. MALDI-TOF MS was performed on these 12 isolates and provided additional species-level identification for 9/12 isolates, including four isolates of T. rubrum, three of T. tonsurans, one of T. interdigitale, and one of M. canis; the remaining three isolates were identified only as Trichophyton spp. According to Sanger sequencing results, the genus Trichophyton predominated, accounting for 36/39 isolates (92.3%), whereas Microsporum accounted for 3/39 isolates (7.7%). The two most common species were T. rubrum with 16/39 isolates (41.0%) and T. tonsurans with 15/39 isolates (38.5%). Conclusions: The genus Trichophyton was the predominant dermatophyte causing onychomycosis, with T. rubrum and T. tonsurans being the two most frequently identified species. Combining conventional methods with MALDI-TOF MS and Sanger sequencing improves the accuracy of dermatophyte species identification, thereby supporting etiological diagnosis and treatment orientation for onychomycosis.
Keywords: Onychomycosis, dermatophytes, Trichophyton, Microsporum, MALDI-TOF MS, Sanger sequencing